1995
DOI: 10.1037/0022-006x.63.3.474
|View full text |Cite
|
Sign up to set email alerts
|

Women's self-disclosure of HIV infection: Rates, reasons, and reactions.

Abstract: A survey of 65 ethnically diverse women at 2 outpatient HIV clinics revealed relatively low rates of disclosure of HIV-positive serostatus to extended family members, somewhat higher rates for immediate family members, and highest rates for lovers and friends. Spanish-speaking Latinas were less likely to disclose their serostatus or to discuss HIV-related worries with others than English-speaking Latinas, African Americans, and Anglo Americans. Reasons for disclosure and nondisclosure varied by target. In gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
108
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 19 publications
15
108
3
Order By: Relevance
“…Although contrary to our original hypothesis, a plausible explanation is simply that frequent disclosure of HIV serostatus increases the likelihood that a person will eventually experience mistreatment and discrimination by allowing a broader range of people to be aware of a person's serostatus. Thus, avoiding serostatus disclosure may limit illness-related social support (Mansergh, Marks, & Simoni, 1995;Simoni et al, 1995), but may also lessen the likelihood that an HIV-positive person experiences overt acts of discrimination. Past experiences of discrimination may well reduce future disclosure of HIV status, an effect that is not detectable in the cross-sectional analyses presented in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although contrary to our original hypothesis, a plausible explanation is simply that frequent disclosure of HIV serostatus increases the likelihood that a person will eventually experience mistreatment and discrimination by allowing a broader range of people to be aware of a person's serostatus. Thus, avoiding serostatus disclosure may limit illness-related social support (Mansergh, Marks, & Simoni, 1995;Simoni et al, 1995), but may also lessen the likelihood that an HIV-positive person experiences overt acts of discrimination. Past experiences of discrimination may well reduce future disclosure of HIV status, an effect that is not detectable in the cross-sectional analyses presented in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people infected with HIV who are integrated into social networks have higher levels of psychological well-being than those who are not. 15 Perceptions of social support are also positively associated with the percentage of friends, family, and sexual partners to whom the diagnosis has been disclosed. 16 This source of support was essential to the wellbeing of all our respondents; the 1 respondent who was not receiving family support was the worst off psychologically and materially.…”
Section: Outcomes Of Disclosurementioning
confidence: 99%
“…34 Studies have also found that delayed disclosure to PHIVþ Latino youth may be explained by cultural norms within Latino families, where certain topics such as HIV/AIDS, sex, and drugs are simply not discussed with younger members of the family. 35,36 Studies have found that acculturation in general plays a role in the timing of HIV disclosure 37 and it has been associated with a greater knowledge of health issues and greater likelihood in utilizing health care resources. 38 Similar to this study's finding, Mason et al 39 found that, when compared to English-Speaking Latino men, Spanish-speaking Latino men were less likely to disclose their HIV status.…”
Section: Disclosure Statusmentioning
confidence: 99%